Concerns, issues and coping strategies of international students in selected private universities in the Philippines - Pabiton, Carmelita P. (2006)
This study assessed the nature of the problems or concerns experienced by international students in two selected universities in the Philippines and the strategies they employed to cope with their concerns/difficulties. Sixty (60) students participated in the study by answering an open-ended questionnaire. Results indicate that common problems/concerns were along academic, personal-social and cultural environmental domains, and these are mainly due to their inadequate orientation to the host country's culture and lack of proficiency in English and/or local (Filipino) languages. Coping strategies were: spending extra time on academic workload; joining study groups; seeking from friends, and consultating with professors and administrators. Implications for counseling programs for international students in the Philippines were discussed.
Keywords: Foreign students -- Life skills assessment; Adjustment (Psychology); Foreign students -- Attitudes